Theoretical Study of Copper Complexes: Molecular Structure, Properties, and Its Application to Solar Cells - Jesus Baldenebro-Lopez; Norma Flores-Holguin; Jose Castorena-Gonzalez; Jorge Almaral-Sanchez; Daniel Glossman-Mitnik (International Journal of Photoenergy)
We present a theoretical investigation of copper complexes with potential applications as sensitizers for solar cells. The density functional theory (DFT) and time-dependent DFT were utilized, using the M06 hybrid meta-GGA functional with the LANL2DZ (D95V on first row) and DZVP basis sets. This level of calculation was used to find the optimized molecular structure, the absorption spectra, the molecular orbitals energies, and the chemical reactivity parameters that arise from conceptual DFT. Solvent effects have been taken into account by an implicit approach, namely, the polarizable continuum model (PCM), using the nonequilibrium version of the IEF-PCM model.